ANALISIS PENGELOLAAN OBAT PADA TAHAP PENGADAAN DI RUMAH SAKIT ROEMANI MUHAMMADIYAH SEMARANG - Chotijah Karimah; Septo Pawelas Arso; Wulan Kusumastuti (Jurnal Kesehatan Masyarakat (Undip), 2020)
Procurement is part of the management of the drug which is very devoted to the supply of drugs and the costs incurred by the hospital. This study discusses the procurement of drugs in the National Health Insurance service in Roemani Muhammadiyah Hospital Semarang. This research is qualitative research with descriptive research supported by secondary data with retrospectives and primary data with in-depth interviews. Procurement is done by electronic purchase via e-catalog and manual which is done twice a week. The process of drug procurement has not gone well because the long-standing response from the supplier, the drug is not available in the e-catalog, the old system is loaded, the related product in the e-catalog is empty, information about the system is not expected to occur, delays in sending drugs, and sending invoices that leave tempo by the counterparty who can request a delay in payment by the hospital. The result showed that drug management had not been fully in accordance with the criteria. It was indicated from 5 measured indicators, two of them had been in accordance with the criteria which was the percentage of the available fund compared with cost planned and the procurement frequency of each drug item. The other 3 indicators had not been in accordance with the criteria which were frequency uncompleted of order list/contract, frequency of delayed rate in payment by the hospital, and percentage of the amount of drug taken with the approved.